Factors Affecting the Marketing Mix and Internal Resources of Central Javanese Consumers to Purchase PTS: Factors Affecting the Marketing Mix and Internal Resources of Central Javanese Consumers to Purchase PTS - Heru Yulianto, Heru Yulianto (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze the influence of marketing mix factors and internal resources on the purchasing decisions of consumers in Central Java who choose higher education. A combination of descriptive and exploratory methods is used along with research factors such as marketing mix, internal resources and purchasing decisions. This study used a technique called structural equation modeling analysis. The results show that the dimensions of product, price, promotion and location contribute to the marketing mix, with the marketing mix contributing the most to promotion. At the same time, resignation factors such as personal characteristics, processes and physical conditions contribute to internal resources, and personal characteristics are the most important factors. Decisions about the type of product, form of product, brand, seller (informant), time of purchase and payment terms contribute to the purchase decision. It turns out that the most important factor is the moment of purchase. Finally, the marketing mix and internal resources contribute to purchase decisions, with internal resources having the greatest influence on purchase decisions